The Role of Gastrointestinal Microbiota in Functional Dyspepsia: A Review - Zhou, Li; Zeng, Yi; Zhang, Hongxing; Ma, Yan (Frontiers in Physiology, 2022)
Functional dyspepsia is a clinically common functional gastrointestinal disorder with a high prevalence, high impact and high consumption of medical resources. The microbiota in the gastrointestinal tract is a large number of families and is one of the most complex microbial reservoirs in the human body. An increasing number of studies have confirmed the close association between dysbiosis of the gastrointestinal microbiota and the occurrence and progression of functional dyspepsia. Therefore, we reviewed the role of dysbiosis of the gastrointestinal microbiota, H. pylori infection and gastrointestinal microbiota metabolites in functional dyspepsia, focusing on the possible mechanisms by which dysbiosis of the gastrointestinal microbiota contributes to the pathogenesis of functional dyspepsia. Several studies have confirmed that dysbiosis of the gastrointestinal microbiota may cause the occurrence and progression of functional dyspepsia by disrupting the biological barrier of the intestinal mucosa, by disturbing the immune function of the intestinal mucosa, or by causing dysregulation of the microbial-gut-brain axis. Probiotics and antibiotics have also been chosen to treat functional dyspepsia in clinical studies and have shown some improvement in the clinical symptoms. However, more studies are needed to explore and confirm the relationship between dysbiosis of the gastrointestinal microbiota and the occurrence and progression of functional dyspepsia, and more clinical studies are needed to confirm the therapeutic efficacy of microbiota modulation for functional dyspepsia.